2021
DOI: 10.21203/rs.3.rs-366384/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and Safety of Remdesivir in COVID-19 Patients: A Retrospective Analysis of Active Surveillance Database

Abstract: Background: Real-world data on safety and efficacy of remdesivir in COVID‑19 management is scant. We present findings of data analysis conducted for assessing the clinical outcomes of remdesivir treatment for COVID-19 in India. Methods: This retrospective analysis used data from an active surveillance programme database of hospitalised patients with COVID-19 who were receiving remdesivir. Results: Of the 2329 patients included, 67.4% were men. Diabetes (29.69%) and hypertension (20.33%) were the most common co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A retrospective cohort study in Korea involving 86 severe COVID-19 patients hospitalized between June 1 and July 31, 2020, suggested better clinical and virologic effectiveness of remdesivir compared to supportive care in the case of mechanical ventilator requirement (22.9 vs. 44.7%, p = 0.032), mechanical ventilator duration (average, 1.97 vs. 5.37 days; p = 0.017), and viral load reduction (increase of cycle threshold (Ct) values: average, 10.19 vs. 5.36; p = 0.007 and the slope of Ct value increase: average, 5.10 vs. 2.68; p = 0.007) ( Joo et al, 2021 ). Another retrospective analysis demonstrated a well-tolerated safety profile of remdesivir and 84% improvement rate of the drug in COVID-19 patients ( Gupte et al, 2021 ). On the contrary, a large observational study in Japan concluded that remdesivir may not have any benefit on hospitalized COVID-19 patients’ clinical outcomes and reductions in need of invasive/non-invasive respiratory support.…”
Section: Introductionmentioning
confidence: 97%
“…A retrospective cohort study in Korea involving 86 severe COVID-19 patients hospitalized between June 1 and July 31, 2020, suggested better clinical and virologic effectiveness of remdesivir compared to supportive care in the case of mechanical ventilator requirement (22.9 vs. 44.7%, p = 0.032), mechanical ventilator duration (average, 1.97 vs. 5.37 days; p = 0.017), and viral load reduction (increase of cycle threshold (Ct) values: average, 10.19 vs. 5.36; p = 0.007 and the slope of Ct value increase: average, 5.10 vs. 2.68; p = 0.007) ( Joo et al, 2021 ). Another retrospective analysis demonstrated a well-tolerated safety profile of remdesivir and 84% improvement rate of the drug in COVID-19 patients ( Gupte et al, 2021 ). On the contrary, a large observational study in Japan concluded that remdesivir may not have any benefit on hospitalized COVID-19 patients’ clinical outcomes and reductions in need of invasive/non-invasive respiratory support.…”
Section: Introductionmentioning
confidence: 97%
“…Mechanical ventilation plays an important role in the world of critical care. The role of mechanical ventilation can be used as a substitute for ventilation in patients with lung disorders (Giusti et al, 2021;Gupte et al, 2022). However, mechanical ventilation can also cause respiratory muscle weakness among patients in the intensive care unit (ICU) (Walsh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%